Hubungan Pengetahuan Tentang Diet Rendah Garam Dengan Sikap Pasien Hipertensi Di Wilayah Kerja Puskesmas Kembang Tanjong Kabupaten Pidie - Nuri Nazari; Yuyun Khairunnisa (Universitas Serambi Mekkah, 2022)
The background of the study: Hypertension caused by high salt consumption. The patients are lack of knowledge about the low- salt diet so that the hypertension suffered them. The purpose of this study: to determine the correlation between the acquaintance of low-salt diet and the hypertension behavioral patients at the public health center at kembang Tanjong. The population was 338 respondents while the sample was 77 respondents by using snowball technique. The questionnaire was used to conduct this research. They were 30 questions. The result showed that the range percentage of the patients' hypertension behavioral was less ( 95.2%). The statistical test results with chi-square obtained P-value 0.004 ≤ 0.05. The conclusion, there is a relationship of knowledge about a low-salt diet with hypertensive behavioral patients. The suggestion, this research can be used as further information about the prevention of a low-salt diet for hypertension patients